Multi-omics analysis of hepatic outcomes in T2DM-MAFLD patients treated with semaglutide: a single-centre, longitudinal, data-driven study - Niu, Shu; Chen, Shuchun; Wu, Di; Wang, Chenxi; Xu, Jianchao; Yin, Jiantong; Zhao, Yubin (Frontiers in Endocrinology, 2025)
BackgroundMetabolic-associated fatty liver disease (MAFLD) is a leading cause of chronic liver disease and is closely linked to type 2 diabetes mellitus (T2DM). The pathogenesis of MAFLD involves complex metabolic imbalances, including impaired fatty acid β-oxidation and chronic inflammation. GLP-1 receptor agonists (GLP-1 RAs) have shown promise in improving metabolic outcomes, but their specific effects on MAFLD remain unclear. This study aims to investigate the molecular mechanisms underlying the hepatic benefits of semaglutide, a GLP-1 RA, in T2DM patients with MAFLD using serum proteomics and metabolomics.MethodsWe conducted a single-centre, longitudinal, data-driven study involving 75 T2DM patients with MAFLD (pre-treatment, PT) and 100 healthy controls (health control, HC). Patients received semaglutide treatment (0.25 mg/week initially, escalated to 0.5 mg/week) for 12 weeks. Serum proteomic and metabolomic profiles were analyzed using 4D-DIA proteomics and LC-MS before and after treatment. Biomarker discovery involved the identification of differential metabolites and proteins, pathway analysis, and integration of proteomic and metabolomic data. Clinical and biochemical parameters were also assessed.ResultsSemaglutide significantly improved metabolic and liver parameters, including HbA1c, BMI, HOMA-IR, liver function, IL-6, and liver stiffness (p < 0.01). Multivariate analysis revealed distinct proteomic and metabolomic profiles between baseline and post-treatment groups. A total of 203 differential metabolites and 61 proteins were identified, with key changes including reductions in long-chain fatty acids and inflammatory mediators, alongside increases in carnitine derivatives and anti-inflammatory proteins. Pathway analysis highlighted effects on fatty acid metabolism, PPAR signaling, and NAFLD-related pathways.ConclusionOur study provides a comprehensive multi-omics analysis revealing that semaglutide modulates serum proteomic and metabolomic profiles in T2DM-MAFLD patients, potentially through enhancing mitochondrial β-oxidation, reducing lipid toxicity, and suppressing inflammation. These findings offer mechanistic insights into the hepatic benefits of semaglutide and support its potential as a therapeutic agent for MAFLD. This innovative approach advances our understanding of GLP-1 RAs’ multi-organ protective effects and provides a foundation for developing precision medicine strategies for MAFLD.